Anxiety symptoms during COVID-19 in older adults with psychiatric disorders - Pongan, Elodie; Rouch, Isabelle; Herrmann, Mathieu; Perrot, Catherine; Lebrun-Givois, Cécile; Spirli, Laurie; Briollet, Chloé; Martin, Hélène Saint; Laurent, Bernard; Bachelet, Romain; El Haouari, Hanane; Buisson, Aurélie; et al. (Frontiers in Psychiatry, 2023)
Objective : During the Covid-19 pandemic, older people and patients with psychiatric disorders had an increased risk of being isolated. The French National Authority for Health has recommended a reinforced follow-up of these patients. Cross-sectional studies reported an increased risk of developing anxiety and depression during pandemic. The aim of our study was to identify factors associated with higher anxiety during the pandemic in older patients with psychiatric disorders. Methods : Steracovid is a multicenter cohort study with 117 patients followed-up by phone in two French geriatric psychiatry units. In this work, we used cross-sectional data from a prospective follow-up conducted between January and May 2021. Results: We found that coping strategies, personality, and living conditions were associated with general anxiety level during the pandemic period. Higher general anxiety was associated with less positive thinking coping strategy, more avoidance strategies, a lower level of extraversion, a higher level of neuroticism, more time spent watching the news, a higher feeling of loneliness, and a lack of physical contact. Findings: Our study identified factors associated with a poorer experience of pandemic crisis. Special attention should be paid to patients with a high level of neuroticism and a high feeling of loneliness. Support could aim to help patients use more functional strategies: reducing avoidance strategies and increasing positive thinking. Finally, reducing time watching news could also be an interesting prevention perspective.